2017
DOI: 10.17240/aibuefd.2017.17.30227-326595
|View full text |Cite
|
Sign up to set email alerts
|

Müzik Öğretmeni Adaylarının Problem Çözme Becerilerinin Piyano Dersinde Karşılaştıkları Sorunların Çözümüne Olan Etkilerinin İncelenmesi

Abstract: ÖZETBu çalışmanın amacı müzik öğretmeni adaylarının problem çözme becerisi (PÇB) algılarını belirlemek ve piyano dersinde karşılaştıkları problemleri çözmede bu algılarının nasıl bir etkisi olduğunu incelemektir. Ayrıca öğrencilerin PÇB algıları cinsiyet ve mezun oldukları lise türüne göre değerlendirilmiş ve piyano dersi başarısı ile arasında anlamlı bir ilişki olup olmadığı araştırılmıştır. Araştırmanın çalışma grubunu, birinci sınıfta öğrenim görmekte olan 35 müzik öğretmeni adayı oluşturmaktadır. Nicel ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The present study did not find any significant differences on the overall scale and in its sub-scales based on gender. The study of Güven (2017) with ten students revealed no significant differences on the overall scale, approach-avoidance style subscale, and personal control subscale. However, there was a significant difference in the problem-solving confidence subscale in favor of the male students.…”
Section: Discussionmentioning
confidence: 81%
“…The present study did not find any significant differences on the overall scale and in its sub-scales based on gender. The study of Güven (2017) with ten students revealed no significant differences on the overall scale, approach-avoidance style subscale, and personal control subscale. However, there was a significant difference in the problem-solving confidence subscale in favor of the male students.…”
Section: Discussionmentioning
confidence: 81%
“…Because the students focused on the option of playing the piece from beginning to end during the synthesis stage and because they did not use different problem-solving options, they lost time and could not solve the musical problem they encountered. Similarly, Güven (2017) stated that the problem-solving skills of music students are low; the most common problems students encounter are technical problems and problems related to tempo. He also stated that he had no problem in defining the problem, but had difficulties in solving it, by expressing the problems they encountered during the piano practice.…”
Section: Discussionmentioning
confidence: 99%
“…Musical problem-solving skills are discussed in study areas such as the study of problem-solving in musical instruments study (McAdams, 2004), the examination of problem-solving and self-regulated learning strategies in musical instruments study (Nielsen, 2001) and the development of problemsolving skills in melodic improvisation (Abdullah et al, 2021). In addition, the problem-solving skills of music students are low (Güven, 2017;Küçük, 2012); problem-solving skills in music education do not differ according to gender (Çevik, 2011;Otacıoğlu, 2008); and the problem-solving skills of music students affect self-confidence and musical instruments success (Otacıoğlu, 2008); it has been investigated in various studies that there is no significant relationship between academic achievement in piano lessons and problem-solving skills (Güven, 2017) and that there is a high level of positive relationship between communication skills and problem-solving skills' sub-dimensions of music students (Küçük, 2012).…”
Section: Related Researchmentioning
confidence: 99%